2017
DOI: 10.1016/j.electacta.2017.03.059
|View full text |Cite
|
Sign up to set email alerts
|

In situ XAFS Study of Palladium Electrodeposition at the Liquid/Liquid Interface

Abstract: We report the use of XAFS (X-ray absorption fine structure) as an in situ method to follow the electrochemically driven deposition of palladium nanoparticles at a liquid/liquid interface.A novel glass/plastic hybrid electrochemical cell was used to enable control of the potential applied to the liquid/liquid interface. In situ measurements indicate that the nucleation of metallic nanoparticles can be triggered through chronoamperometry or cyclic voltammetry.Page 2 of 37 A c c e p t e d M a n u s c r i p tIn co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Coupled in situ X-ray fluorescence (XRF) and X-ray absorption fine structure (XAFS) techniques monitored the gold nucleation and NPs growth at an electrified interface, which supported the formation of spherical gold NPs aggregates described by ex situ studies reported in earlier publications (see Figure 7B) [142]. Furthermore, in-situ XAFS was used to describe the growth and deposition of Pd NPs suggesting a direct two electron reduction of [PdCl4] 2to Pd 0 followed by the formation of stable Pd clusters [144]. Certainly, a better understanding of the NPs growth dynamics at a molecular scale during the interfacial electrodeposition is desirable.…”
Section: Metal Nanoparticlessupporting
confidence: 79%
“…Coupled in situ X-ray fluorescence (XRF) and X-ray absorption fine structure (XAFS) techniques monitored the gold nucleation and NPs growth at an electrified interface, which supported the formation of spherical gold NPs aggregates described by ex situ studies reported in earlier publications (see Figure 7B) [142]. Furthermore, in-situ XAFS was used to describe the growth and deposition of Pd NPs suggesting a direct two electron reduction of [PdCl4] 2to Pd 0 followed by the formation of stable Pd clusters [144]. Certainly, a better understanding of the NPs growth dynamics at a molecular scale during the interfacial electrodeposition is desirable.…”
Section: Metal Nanoparticlessupporting
confidence: 79%
“…42 Dryfe et al prepared Pd nanoparticles at the O|W interface by externally controlling the phase boundary potential across the O|W interface. 37,[43][44][45][46] Recently, growing interest has been drawn on replacing organic solvents by hydrophobic ionic liquids (ILs) in the L|L interfacial method. [47][48][49][50] ILs are liquid salts which are entirely composed of cations and anions.…”
Section: Introductionmentioning
confidence: 99%
“…prepared Pd particles by a heterogeneous redox reaction at the O|W interface and then applied the interfacial Pd nanoparticles as reductive photocatalysts for a photoinduced two-phase redox reaction . Dryfe et al prepared Pd nanoparticles at the O|W interface by externally controlling the phase boundary potential across the O|W interface. , …”
Section: Introductionmentioning
confidence: 99%
“…The technique has recently been shown to be able to detect the formation of prenucleation equilibrium during the reactive interfacial nucleation of metal nanoparticles. [13][14][15] The involvement of valence levels makes NEXAFS also highly sensitive to chemical and physical changes around organic molecules in solution and in the solid state. Differences due to crystal polymorphism, 16 solute-solvent interactions, [17][18][19] protonation and hydrogen bonding 18,20,21 have been reported.…”
Section: Introductionmentioning
confidence: 99%